Electrical and optical properties of phosphorene graphene added polyvinylidene fluoride nanocomposites - Harun, Marziana (2024)
Phosphorene/graphene-incorporated polyaniline nanocomposites have been synthesised by mechano-sonic techniques. Phosphorene, a fascinating twodimensional substance with a puckered-layer structure, was invented to increase the energy storage capacity and preserve the electrical conductivity of graphene by infiltrating it between the layers of graphene. The nanocomposites acquired semiconductor characteristics as a result of the incorporation of the additives, which created an energy band gap in phosphorene. This study examines the impact of incorporating phosphorene into nanocomposites, with polyaniline acting as the matrix, on the electrical conductivity and optical band gap. The ratio of phosphorene to graphene in the mixture ranged from 0.2:1 to 1:1. The 2D nanomaterials were blended together using a high-energy planetary ball mill operating at a speed of 450 revolutions per minute for a duration of one hour. Afterwards, the powder that was prepared earlier was separated into layers using a centrifugal rotating machine in n-methyl-2- pyrrolidone. The separated layers were then mixed with polyaniline using an ultrasonic bath. Phosphorene and graphene were detected in each sample using XRD and Raman analysis. The FESEM microstructure images clearly showed two different layers, which were recognised as graphene and phosphorene profiles using EDX. The examination using UV-vis spectroscopy showed that the nanomaterials, when suspended in n-methyl-2-pyrrolidone, have an energy bandgap ranging from 1.38 eV to 2.28 eV. FESEM measurements revealed that the microstructure exhibited increased density, while the inter-grain boundaries displayed a smoother texture. These changes resulted in a reduction in graphene segregation and the creation of pathways for electrons.